Dicer Assay in Drosophila S2 Cell Extract. - Yang, B.; Li, H. (Methods in Molecular Biology (New York), 2011)
Double-stranded RNA (dsRNA) is the trigger of RNA interference (RNAi)-mediated gene regulation. Dicer processes dsRNAs into short interfering RNAs (siRNAs), which are incorporated into the effector RNA-induced silencing complex (RISC) and direct degradation of homologous target mRNAs. In plants and invertebrates, the RNAi machinery also acts as an antiviral mechanism through production of viral siRNAs by Dicer and silencing of replicating viruses. Viral suppressors of RNAi (VSRs) are encoded by some viruses and serve as a strategy to counteract the RNAi-based antiviral immunity. In this chapter, we describe a Dicer activity assay in extracts prepared from Drosophila melanogaster S2 cells. We also introduce a simple procedure to study VSR activity in the in vitro Dicer assay.